PERAN GURU DALAM MENSTIMULUS PERKEMBANGAN KOGNITIF ANAK USIA DINI DI TK DHARMA WANITA - Hotimah, Raniyatul; Tsani, Mutiara; Watin, Suhela; Latif, Muhammad Abdul (STAINU Purworejo, 2023)
Early Childhood Education (ECE) plays a central role in shaping the foundational development of children from an early age, with a primary focus on the role of teachers. This research aims to systematically describe the learning approach and the role of teachers in stimulating cognitive development in children at TK Dharma Wanita Petiyintunggal. A descriptive research method is employed to illustrate the facts and characteristics of the research object. The results reveal that the learning approach in this kindergarten intensely emphasizes cognitive development, with teachers committed to fostering language skills, abstract thinking, and creativity through educational activities. The teacher's role involves designing effective teaching strategies, implementing developmentally appropriate teaching methods, and continuous efforts to enhance cognitive stimulation through collaboration and parental involvement. Teacher recommendations for improving training, integrating technology, and strengthening collaboration emerge as crucial steps in refining the cognitive stimulation approach for children in this kindergarten.